New Tendencies in Criminal Organization and Geographical Mobility. Geopolitical Approach and Criminal Intelligence - Sansó-Rubert Pascual, Daniel (UNISCI Journal, 2016)
This article aims to provide an explanatory introduction to the types of possible relationships in the organized criminal field, organizational models and geographical mobility, through the conjunction of the disciplines of criminology, geopolitics and criminal intelligence. The study has two objectives: first, to provide a reflection that favors the opening of research on the morphological diversity of criminal organizations, the alliances forged between them as well as their territorial expansion, and second, maximizing the knowledge in order to support the strategic decision-making, public policy and detection of exploitable vulnerabilities for the development of intervention strategies.